Modelltheorie: 21.01. bis 27.01.1990 - Dries, Lou van den; Prestel, Alexander; Roquette, Peter (Tagungsbericht, 1990)
Andreas Baudisch; Luc Belair; Ralph Berr; Elisabeth Bouscaren; Michel Brestovski; Ludwig Bröcker; Zoe Chatzidakis; Bernd-Ingo Dahn; Paola D'Aquino; Francoise Delon; Max A. Dickmann; Lou van den Dries; Jean-Louis Duret; Yuri L. Ershov; Ulrich Felgner; Gerhard Frey; Michael David Fried; U. Friedrichsdorf; Wulf-Dieter Geyer; Barry William Green; Dan Haran; Moshe Jarden; Christian Ulrik Jensen; Manfred Knebusch; Franz-Viktor Kuhlmann; Urs-Martin Künzi; Angus John MacIntyre; David Marker; Michel Matignon; Margarita Otero Dominguez; Evgenii A. Paljutin; Johan Pas; Thanases Pheidas; Anand Pillay; Bruno Poizat; Florian Pop; Alexander Prestel; Joachim Reineke; Peter Roquette; Philipp Rothmaler; Robert S. Rumely; Joachim Schmid; Niels Schwartz; Philip Scowcroft; Volker Weispfenning; Carol Wood; Martin Ziegler